The Comitology Game: European Policymaking with Parliamentary Involvement - Bernard Steunenberg; Dieter Schmidtchen (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 2000)
This paper discusses institutional reforms that might strengthen the role of the European Parliament in the policymaking process of the European Union. Using simple game theory, the paper analyzes the working properties of the different implementation procedures that are known as 'comitology'. The Council of the European Union employs these procedures when it delegates some of its policymaking power to the Commission as part of Union legislation. We show how the balance of power is determined by the current comitology procedures, and how this balance would change if the role of the European Parliament were strengthened in the comitology game. – – Dieser Beitrag diskutiert institutionelle reformen, die die Rolle des Europäischen Parlaments im Entscheidungsprozeß der Europäischen Union stärken können. Mit Hilfe eines einfachen spieltheoretischen Modells wird der Wirkungsmechanismus verschiedener unter dem Stichwort Komitologie bekannter Implementationsprozeduren analysiert. Der Rat wendet diese an, wenn er im Rahmen des EU-Gesetzgebungsprozesses seine Entscheidungsgewalt zum Teil der Kommission überträgt. Wir zeigen, wie das Machtgleichgewicht durch die geltenden Komitologie-Prozeduren bestimmt wird und wie sich dieses Gleichgewicht verändern würde, wenn die Stellung des Parlamentes gestärkt würde.
Keywords: D72; 330; Strategic power index; comitology; balance of power; Politische Entscheidung; Spieltheorie; Macht; Gewaltenteilung; Parlament; Theorie; EU-Politik; EU-Staaten